Uncovering homo-and hetero-interactions on the cell membrane using single particle tracking approaches. (8th February 2016) - Torreno-Pina, Juan A; Manzo, Carlo; Garcia-Parajo, Maria F
Abstract: The plasma membrane of eukaryotic cells is responsible for a myriad of functions that regulate cell physiology and plays a crucial role in a multitude of processes that include adhesion, migration, signaling recognition and cell–cell communication. This is accomplished by specific interactions between different membrane components such as lipids and proteins on the lipid bilayer but also through interactions with the underlying cortical actin cytoskeleton on the intracellular side and the glycocalyx matrix in close proximity to the extracellular side. Advanced biophysical techniques, including single particle tracking (SPT) have revealed that the lateral diffusion of molecular components on the plasma membrane represents a landmark manifestation of such interactions. Indeed, by studying changes in the diffusivity of individual membrane molecules, including sub-diffusion, confined diffusion and/or transient arrest of molecules in membrane compartments, it has been possible to gain insight on the nature of molecular interactions and to infer on its functional role for cell response. In this review, we will revise some exciting results where SPT has been crucial to reveal homo- and hetero-interactions on the cell membrane.